Record of Pompilidae (Hymenoptera, Pompiloidea) in a deciduous forest in Minas Gerais, Brazil - Gabriel de Castro Jacques; Marcos Magalhães de Souza; Fernando Gonçalves de Aguiar Crispim (Revista Agrogeoambiental, 2023)
There is little information about the Pompilidae fauna in Brazil’s Deciduous Forests and no reports about how this taxon manifests itself in the Mata Seca State Park (PEMS), which is considered one of the most important for the protection of this forest in Brazil. This work was carried out to record the occurrence of Pompilidae in the Deciduous Forest of the PEMS. The records were occasionally taken in the PEMS during 24 days in 2021. A total of 16 individuals of two genera, four species, and three morphospecies of Pompilidae were collected. The Pepsis albocincta Smith, 1855; Pepsis apicata Taschenberg, 1869; Pepsis decorata Perty, 1833; and Entypus taschenbergii (Dalla Torre, 1897) species are new to Brazil’s dry forest, which reaffirms the importance of the PEMS in ensuring the protection of biological diversity in the Deciduous Forests of Brazil.